Developmental sequences for observing and assessing forceful kicking. (August 2021) - Sacko, Ryan S.; Utesch, Till; Cordovil, Rita; De Meester, An; Ferkel, Rick; True, Larissa; Gao, Zan; Goodway, Jacqueline; Bott, Tim S.; Stodden, David F.
While football/soccer is the most influential sport in the world, it is surprising that developmental sequences of forceful kicking have not been adequately described and validated in the literature. The purpose of this study was to explore potential developmental sequences for forceful kicking using a prelongitudinal screening method. Data were derived from videotapes of 255 children (girls n = 138, boys: n = 117), ages 4–11 years. Seven potential component sequences in their respective developmental order were initially proposed based on biomechanical and motor developmental principles. Each participant was digitally videoed performing five kicks with maximal effort. Trained research staff coded the initial seven components for each kick and the mode of each participant's five kicks was used for data analysis. Component level probability curves for each component sequence across age were evaluated using the threshold based generalized partial credit model (Muraki, 1992) within the item response theory framework. As developmental theory would indicate, component levels generally increased with age for most components. Six component ordinal sequence progressions met model requirements (Rel = 0.88, item fit; p > 0.05). Ordinal levels for two components ( Knee action and Follow-through ) were altered based on initial empirical model structure fit and the Ball contact component was removed based on a lack of model fit. This study provides sufficient cross-sectional evidence for six component developmental sequences that adequately describe the development of kicking using cross-sectional data. Longitudinal data are required to provide further developmental validation for these sequences.